The multipotent thidiazuron: A mechanistic overview of its roles in callogenesis and other plant cultures in vitro. (8th February 2022) - Ali, Haroon Muhammad; Khan, Tariq; Khan, Mubarak Ali; Ullah, Nazif
Abstract: Thidiazuron (TDZ) is an active substituted phenyl urea compound that has found a significant role as a plant growth regulator. The most exciting aspect of its function is that it can mimic auxins and cytokinin but is chemically different from these two. Many theories have been put forward, and experiments performed to understand the mode of action of TDZ in callogenesis. One suggested mechanism presents that it works by inhibiting the cytokinin degrading enzymes that compete with cytokinin for an active site on the enzyme. An example is the TDZ‐induced suppressed expression of gibberellic acid (GA) biosynthesis genes encoding GA3 and GA20 oxidases . This is entailed with a slightly increased expression of GA catabolism genes encoding GA20 oxidase . Similarly, one of the recommendations is that TDZ induces the expression of specific genes and transcription regulatory sequences that are either responsible directly for callus formation or in turn induce other auxins or cytokinin for callogenesis. There is no concise review available that discusses the details of TDZ‐induced callus, specifically and other in vitro cultures in general. This review is an attempt to explore all these pathways and mechanisms involved in callogenesis in plants stimulated by TDZ. Abstract : Illustration representing the mechanism of action of thidiazuron